2004
DOI: 10.1029/2004jb003030
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of electrical conductivity and structural damage at a major strike‐slip fault in northern Chile

Abstract: [1] Large-scale strike-slip fault zones are often imaged as electrically conductive structures in the brittle crust. However, the relationship of conductivity and internal architecture of the fault zone remains largely unclear. This paper presents results of a study designed to compare the record of structural deformation across a fault zone with its electrical conductivity image. Two high-resolution magnetotelluric profiles trend perpendicularly across the West fault, a branch of the Precordilleran fault syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Becken et al (2008) imaged the deep resistivity structure (surface-25 km) near the San Andreas Fault Observatory at Depth (SAFOD) and also pointed out the presence of FZC. MT images for the West Fault in northern Chile confirmed earlier studies and showed FZCs (Hoffmann-Rothe et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Becken et al (2008) imaged the deep resistivity structure (surface-25 km) near the San Andreas Fault Observatory at Depth (SAFOD) and also pointed out the presence of FZC. MT images for the West Fault in northern Chile confirmed earlier studies and showed FZCs (Hoffmann-Rothe et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Both Ritter et al (2005) and Hoffmann-Rothe et al (2004) presented tables for comparing FZC properties of various faults. These properties include the activeness of the fault segment, and the width and depth of the FZC, as well as the lateral conductance (lateral conductance = the width of the conductor × average conductivity), observed in relation to the FZC (see the discussion in Ritter et al (2005) on lateral conductivity; page 170).…”
Section: Comparison Between Fzcs On Other Faultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated conductivities surrounding the uppermost portion of the fault were also imaged at Carrizo plain, though as a less pronounced feature of the resistivity model ( Figure 5a). Such a fault-zone conductor (FZC), prominently apparent at Parkfield and Hollister, and modest at Carrizo Plain, is believed to correspond to saline fluid circulation within the damage zone of the fault and appears to be typical for the SAF and for many other faults worldwide (Ritter et al 2005;Hoffmann-Rothe et al 2004).…”
Section: The Fault Zone Conductormentioning
confidence: 99%
“…Thus, low resistivity zones at subsolidus temperatures are often interpreted as porous zones with fluid. For example, the observed low resistivity images along the faults could be explained as the existence of an abundant quantity of fluid in cracks or fault breccias (e.g., Unsworth et al, 1997;Hoffmann-Rothe et al, 2004). Recent magnetotelluric (MT) investigations have also revealed low resistivity zones distributed in the mid to lower crust beneath the intraplate earthquake zones (e.g., Mitsuhata et al, 2001;Ogawa et al, 2001;Ogawa and Honkura, 2004;Wannamaker et al, 2004;Uyeshima et al, 2005;Yoshimura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%